THE LIVING HADITH PHENOMENON IN BANJAR SOCIETY: Integrating Ritual Devotion and Social Solidarity in the Al-Ma’sum Majelis Dhikr and Syarikat Kematian (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2025)
This study aims to analyze the practices of the Majelis Dhikr and Syarikat Kematian Al-Ma’sum at the Al-Ma’sum Mosque in Barabai, Banjar, as a representation of the Living Hadith phenomenon within the Banjar community. Utilizing a qualitative-descriptive approach, this research explores how Prophetic traditions are internalized into local customs to fortify both spiritual and social dimensions. The findings demonstrate that the integration of collective dhikr rituals every Wednesday night with an organized funeral assistance system creates a harmony between the dimensions of hablun min Allah (relationship with God) and hablun min al-nas (relationship among humans). The practice of